Comparative studies on feed efficiency and body conformation characteristics in RIR chicken and its crosses - DAS, ANANTA KUMAR; KUMAR, SANJEEV; RAHIM, ABDUL; DEBNATH, JOWEL; KOKATE, LAXMIKANT SAMBHAJI (The Indian Journal of Animal Sciences, 2023)
The feed efficiency and body conformation characteristics were evaluated in 457 chicks of RIR-selected, controland white strains, CARI-Sonali and CARI-Debendra crossbred chicken maintained at ICAR-Central Avian ResearchInstitute. The least squares means of live body weight gain, feed consumption, FCR, shank length, keel length andbreast angle were estimated at various periods of ages. CARI-Debendra recorded significantly the highest live weight gains and FCRs than the other genotypes studied, though RIR-white strain outperformed CARI-Debendra in terms of FCRs at 8th and 16th week of age. CARI-Sonali significantly followed CARI-Debendra in attaining live weight gain up to 8th week of age and thereafter, RIR-selected strain exhibited better weight gain than the CARI-Sonali. CARIDebendra demonstrated better FCRs throughout the ages excepting 8th and 16th week-estimates where RIR-white strain performed the best. RIR-control strain had the least weight gains and non-beneficial FCRs throughout the ages. The male birds had more live weight gains than the females throughout the ages. The best body conformation estimates were found in CARI-Debendra followed by RIR-selected strain/ CARI-Sonali, RIR-white and RIR-control strain. The body conformation estimates of CARI-Sonali were better than that of RIR-selected strain up to 8th week of age, and were found better in males than the females throughout the ages. The findings on genotypic variation in feed efficacy and body conformation characteristics of the birds could be important to the farmers for selection of genotypes for rearing as per their preference of the traits.